Respuesta :

Consider, pls, this option.
Modify solution design according own requirements.
Ver imagen evgeniylevi

The general solution will be "[tex]y = e^{\frac{-x}{3} } (c_1 cos(\frac{\sqrt{2} }{3} x)+ (c_2 cos(\frac{\sqrt{2} }{3} x))[/tex]".

Given:

  • [tex]3y'' +2y'+y =0[/tex]

By writing it in operator form, we get

→ [tex](3D^2+2D+1)y =0[/tex]

Auxiliary equation will be:

→ [tex]3m^2+2m+1=0[/tex]

The roots will be:

→ [tex]m = \frac{-1 \pm \sqrt{4-12} }{2\times 3}[/tex]

       [tex]= \frac{-2 \pm 2\sqrt{2}i }{2\times 3}[/tex]

       [tex]= -\frac{1}{3} \pm \frac{\sqrt{2} }{3} i[/tex]

Thus the above answer is right.  

Learn more about differential equation here:

https://brainly.com/question/353770

ACCESS MORE
EDU ACCESS
Universidad de Mexico